Clinical study of enterocutaneous fistula - Garale, Mahadeo Namdeo; Takalkar, Yogesh Prabhakar; Venkatramani, Karthik (International Surgery Journal, 2017)
Background: An enterocutaneous fistulae (ECF) may be challenging to manage due to the large volume of fluid losses, that may result in severe dehydration, electrolyte imbalances, malnutrition and sepsis. It is imperative that this group of patients receive adequate nutrition, as malnutrition and sepsis are the leading cause of death. Methods: This descriptive study was conducted prospectively in the Department of Surgery between September 2004 and August 2010. Patients whom develop ECF after surgery were included in the study while patients with esophageal, biliary, pancreatic, and perianal fistulas were excluded. The description of fistula included cause, anatomical location, fistula output, complications, and outcome. Fistula output was quantified by direct measurement, in the presence of drain or by calculating number of dressing pads soaked per day. To examine the statistical significance of association between attributes, Chi-square test and Fisher’s exact test were used. A probability value of less than 5% (P < 0.05) was considered significant. Results: A total of 42 patients were included in the study, of which 23 were males and 19 were females and the male:female ratio was 1.2:1. Most patients with ECF were aged 41-50 (mean age, 44.23±2.72). Of the 42 patients, 9 patients had colonic fistula and the remaining had small intestinal fistula; 16 ileal, 5 duodenal, and 12 jejunal. There were 22 patients with high-output fistula as compared to 20 patients with low output fistula. Mortality was significantly higher in patients with males, age >60 years, high-output fistula, mesenteric ischemia as underlying pathology, serum albumin <2.5g/dl and re-surgery. Conclusions: Early diagnosis and stabilization form key aspects of management of ECF as most patients are managed conservatively. Prompt nutritional supplementation alters the outcome of this disease. High output fistulae required mostly surgical management and had high morbidity and mortality.